Ann Clin Endocrinol Metabol 2017
DOI: 10.29328/journal.acem.1001004
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and red blood cell parameters

Abstract: Type 2 diabetes is a common disease in these days and day by day it is arising. The main focus of the study was to investigate association of packed cell volume (PCV), Mean Corpuscular Volume (MPV), Mean Corpuscular Hemoglobin Concentration (MCHC), Red Cell Distribution Width (RDW) with glycemic marker HbA1c. So that PCV, MPV, MCHC, RDW could be used as a predictor of glucoregulation in type 2 diabetes instead of HbA1c value. This study included 87 DMT2 patients, which divided into two groups, A (n=41, presenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 37 publications
5
12
0
1
Order By: Relevance
“…This finding agrees with Sheikhpour et al (2013), who reported a significant relationship between HbA1c and RBC count in T2DM patients (26) . These findings are also in line with the study conducted by Jaman et al ( 2018), who studied different haematological parameters in patients with T2DM (25) . This finding is again in line with a study conducted by Li et al (2015), who concluded a significant direct relationship between HbA1c and RBC count in patients with T2DM.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This finding agrees with Sheikhpour et al (2013), who reported a significant relationship between HbA1c and RBC count in T2DM patients (26) . These findings are also in line with the study conducted by Jaman et al ( 2018), who studied different haematological parameters in patients with T2DM (25) . This finding is again in line with a study conducted by Li et al (2015), who concluded a significant direct relationship between HbA1c and RBC count in patients with T2DM.…”
Section: Discussionsupporting
confidence: 92%
“…This finding reveals that blood donation leads to a decrease in RBC count, resulting in increased plasma components in the whole blood, which finally prevents dehydration and decreases blood viscosity, which in turn causes increased blood flow. Decreased blood hemodynamics has been known as one of the risk factors for the development of diabetes (25) .…”
Section: Discussionmentioning
confidence: 99%
“…However, in contrast to our finding, a study conducted in Bangladesh reported no significant mean difference of RBC count between poor and good glycemic controlled T2 DM patients (p=0.608), and no correlation to HbA1c level. 30 The possible hypothesis for this difference might be due to the relatively small sample size used in the previous study. In the present study, the HGB level was significantly reduced in T2 DM patients with PGC ( Table 2 ).…”
Section: Discussionmentioning
confidence: 90%
“… 34 However, in contrast to the current finding, a study conducted in Bangladesh reported no significant (p=0.2) mean difference of RDW was observed between poor and good glycemic control T2 DM patients, although a positive correlation was detected between RDW and HbA1c level. 30 The discrepancy might be due to differences in the glycemic status of the study population, relatively well-controlled T2 DM patients were enrolled in the previous study.…”
Section: Discussionmentioning
confidence: 99%
“…However, this study did not find a significant association between RDW and HbA1C levels, which is in contrast to studies conducted in Pakistan 17 and Bangladesh. 13 Chronic hyperglycemia associated with DM affects the deformability of RBCs and reduces their life span. A shorter life span of RBCs leads to lower HbA1c levels because the duration of exposure to hyperglycemia is reduced for newly replaced erythrocytes.…”
Section: Discussionmentioning
confidence: 99%